Crypto Forecast: Integrating Web Scraping and Data Analysis for Cryptocurrency Price Prediction - Gadge, Krutika; Daduria, Shreyash; Sarodaya, Abhishek; Borkar, Pradnya Sulas; Badhiye, Sagarkumar Shridhar; Agrawal, Pratik K (Society of Visual Informatics, 2025)
Accurately predicting cryptocurrency prices is still a difficult task because of the extremely volatile nature of the market. This study introduces a new methodology combining web scraping, data analysis, and machine learning to further improve prediction accuracy. A live cryptocurrency monitors gathers data from various sources such as trading volumes, price volatility, and sentiment in market to create a rich data set. Feature engineering is used to convert raw data into useful inputs for machine learning algorithms to further enhance prediction functions. Utilizing Python libraries including Beautiful Soup, Pandas, Scikit-learn, and deep learning libraries, the correct predictive model is designed and strictly tested for precision, performance, data quality, usability, scalability, and cost. The proposed hybrid model is a combination of traditional statistical methods with deep learning models to overcome the constraints of conventional forecasting methodologies. The output reflects the performance of the model in identifying the trends in the market and rendering data-driven insights to traders and investors. Future studies can employ different data sources, including social media sentiment analysis, financial news articles, and web-based cryptocurrency forums, to enhance predictability. Further advancement in time series forecasting through deep learning models, including transformer models, may also enhance the precision of long-term forecasting. A deeper insight into how external forces, including government intervention, macroeconomic trends, and emerging blockchain technologies, would complement our understanding of cryptocurrency market dynamics. This study contributes to complementing predictive analytics in financial markets by providing useful insights to investors, researchers, and policymakers.